The Envoys of Phywa to Dmu (PT 126) - Hill, Nathan (My University, 2021)
New are the texts which offer a glimpse into Tibet’s religious traditions as they existed before the adoption of Buddhism as the state religion in 762. With the exception of stone inscriptions the earliest extant texts in the Tibetan language come from the library cave at Duhuang. Among those extant texts valuable for the study of the indigenous religion, which include descriptions of funerary rituals and Buddhist texts aimed at discouraging more ancient practices, mythological texts per se are quite rare. The Envoy of Phywa to Dmu (Pélliot Tibétain PT 126), a narrative describing the doings of gods in a mythical past, is consequently of paramount importance as evidence for the ancient Tibetan religion. For most of the twentieth century the difficulty of the texts and their physical availability significantly constrained the study of Old Tibetan texts. The research of scholars like Stein and Macdonald generally treated a number of Dunhuang texts at once, without providing detailed studies of individual texts. The increasing understanding of the Old Tibetan language and increasing availability of editions of the texts now allows for more systematic study; the text treated here is no exception to this pattern. The text is treated in passing in French and brief passages are treated in English, but more recent detailed study of the document is only available in Japanese5 and Chinese. Western Tibetology does not pay sufficient attention to Japanese and Chinese scholarship on Tibet. In Old Tibetan studies the bulk of scholarship is now produced in these languages. This study relies in particular on the two essays of Ishikawa, which provide a complete transliteration, translation and discussion of contents and the first complete translation of this text by Chu Junjie. I consult previous literature in a supplementary manner as appropriate. When a complete version of this study was already prepared, I gained access to Drikung, and have incorporated its findings as seemed appropriate.
PUBLISHED
Keywords: Manuscript, Book and Print Cultures